Maciej Jakub Zieliński, „Open pension funds as economic actors of social security in a context of freedom of movement of capital and freedom to provide services in the European Union”, Publisher: C.H. Beck, Warsaw 2016, ISBN 978-83-255-8577-8, pp. 261 - Jacek Wantoch-Rekowski (Prawo Budżetowe Państwa i Samorządu)
This review provides an analysis and an evaluation of the monograph „Open pension funds as economic actors of social security in a context of freedom of movement of capital and freedom to provide services in the European Union”.